Análisis de los principios de igualdad y trato justo en el régimen de compras públicas aplicado a pequeñas y medianas empresas. - Asitimbay Lema Jessica Paola (2025)
The present legal research work, titled "Analysis of the Principles of Equality and Fair Treatment in the Public Procurement Regime Applied to Small and Medium-Sized Enterprises", aims primarily to analyze how the constitutional principles of equality and fair treatment are implemented in Ecuadorian regulations and how they impact the access of small and medium-sized enterprises to public procurement opportunities. The national public procurement system represents a fundamental tool for the economic and social development of the Ecuadorian state, given its capacity to promote inclusion and foster the growth of strategic sectors, such as small and medium-sized enterprises, which constitute the backbone of Ecuador’s productive apparatus. The historical background of this topic dates back to the evolution of Ecuadorian public procurement legislation, which has undergone significant changes since the enactment of the Montecristi Constitution in 2008. This legal framework established fundamental principles, such as equality and transparency, applicable to the public procurement system. With the implementation of the Organic Law of the National Public Procurement System, the aim was to ensure an equitable regime that facilitates the participation of small and medium-sized enterprises, recognizing their key role in job creation and economic dynamism. However, despite these regulatory advances, several issues persist that hinder the effective inclusion of in procurement processes, revealing barriers to access, inequality in contract awards, and limited state oversight in the application of the principles of fair treatment. The main objective of this research is to analyze, from a legal perspective, the Ecuadorian regulations applicable to public procurement, assessing their consistency with the principles of equality and fair treatment and their impact on small and medium-sized 6 enterprises. To achieve this, a qualitative methodological approach is used to interpret and understand the legal framework, constitutional principles, and their practical implementation. From a theoretical standpoint, a dogmatic analysis of the principles of equality and fair treatment enshrined in the Constitution of the Republic of Ecuador is conducted, contrasting them with the specific provisions of the Organic Law of the National Public Procurement System and its regulations. This research also incorporates explanatory elements by exploring the structural and regulatory causes that hinder the effective and, above all, equitable inclusion of small and medium-sized enterprises in public procurement processes. To carry out this study, research techniques and tools have been defined, including documentary analysis of laws, regulations, and judicial rulings; and semi-structured interviews with key actors, such as public officials in charge of procurement in their institutions and representatives of small and medium-sized enterprises. The proposed methodological approach is based on the use of inductive, deductive, and analytical methods. The inductive method allows general conclusions to be drawn from the analysis of specific public procurement cases, while the deductive method starts from constitutional principles to assess their practical implementation. Documentary analysis enriches the study by identifying both advancements and shortcomings in the Ecuadorian system. Keywords: Public procurement, SMEs, Public contracting, Economic inclusion, Economic development, Productive apparatus.